S-index and soybean root growth in different soil textural classes - Pedro D. de Oliveira; Michel K. Sato; Sueli Rodrigues; Herdjania V. de Lima (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study tested the hypothesis that the limiting values of S-index, proposed in the literature can not be used to determine the degradation condition of soils under soybean cultivation in the state of Pará, Brazil. The objective was to determine limiting values of S-index using soil physical attributes and validate it with soybean root growth, in soils with different textural classes. For the experimental design, the following treatments were established: five compaction levels for sandy loam and sandy clay loam soils and three levels for clayey and very clayey soils. The following physical parameters were analysed: particle-size distribution, soil bulk density, critical soil bulk density, degree of compaction, soil-water retention curve, S-index and relative root length of soybean. The limiting values of S-index varied according to soil textural class and were equal to 0.037, 0.020 and 0.056 for sandy loam, sandy clay loam and clay, respectively. The S-index does not apply to soils with clay content > 71%, because it does not vary with the degree of compaction of the soil or the root growth of the evaluated crop.